Antimicrobial Growth Promoters Used in Animal Feed: Effects of Less Well Known Antibiotics on Gram-Positive Bacteria - Butaye, Patrick (American Society for Microbiology, 2003)
There are not many data available on antibiotics used solely in animals and almost exclusively for growth promotion. These products include bambermycin, avilamycin, efrotomycin, and the ionophore antibiotics (monensin, salinomycin, narasin, and lasalocid). Information is also scarce for bacitracin used only marginally in human and veterinary medicine and for streptogramin antibiotics. The mechanisms of action of and resistance mechanisms against these antibiotics are described. Special emphasis is given to the prevalence of resistance among gram-positive bacteria isolated from animals and humans. Since no susceptibility breakpoints are available for most of the antibiotics discussed, an alternative approach to the interpretation of MICs is presented. Also, some pharmacokinetic data and information on the influence of these products on the intestinal flora are presented.